Improved Magnetorheological Properties by Using Ionic Liquid as Carrier Liquid of Magnetorheological Fluids - Tong, Yu; Li, Xiaoguang; Zhao, Penghui; Dong, Xufeng; Wu, Zhanjun; Qi, Min (Frontiers in Materials, 2021)
The interface between the particles and the carrier fluids has an important influence on the performance of magnetorheological fluid (MRF). In this study, ionic liquids and silicone oils with the same viscosity and different surface tensions were used as carrier fluids to prepare two different carbonyl iron powder (CIP) magnetorheological fluids. The rheological properties of the two magnetorheological fluids were evaluated by the MCR301 rotating rheometer. The experimental results indicate that ionic liquid-based MRF showed higher shear yield strength and more significant MR effect than silicone oil-based ones in higher magnetic field strength. A possible explanation was proposed and proved through experimental data analysis.